2011
DOI: 10.1002/jsfa.4744
|View full text |Cite
|
Sign up to set email alerts
|

Development of colour and firmness in strawberry crops is UV light sensitive, but colour is not a good predictor of several quality parameters

Abstract: Although surface colour of strawberry fruits was affected by the UV regime during growth, and this parameter is an important factor in consumer perception, we concluded that the surface colour at the time of harvest was, contrary to consumer expectations, a poor indicator of firmness, potential shelf life or anthocyanin content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Especially UV light but also other specific light qualities, e.g. blue light, has been associated with regulation of anthocyanin biosynthesis in fruits [63,64,65]. High temperatures (30°-35°C) have been shown to decrease anthocyanin content in the skin of apple and grapevine berries [62,66,67].…”
Section: Environmental Regulation Of Anthocyanin Biosynthesismentioning
confidence: 99%
“…Especially UV light but also other specific light qualities, e.g. blue light, has been associated with regulation of anthocyanin biosynthesis in fruits [63,64,65]. High temperatures (30°-35°C) have been shown to decrease anthocyanin content in the skin of apple and grapevine berries [62,66,67].…”
Section: Environmental Regulation Of Anthocyanin Biosynthesismentioning
confidence: 99%
“…8,9 UV wavelengths may also affect other ripening-related parameters, such as firmness, which, in strawberries, is affected by changes in the UV wavelengths transmitted by polythene films in protected cultivation. 10 Similarly, tomato firmness was influenced by post-harvest UV-B treatments, either in a positive 11 or in a negative way. 8 However, information on the effects of post-harvest UV treatments on fruit cell wall metabolism is scarce and limited to the use of UV-C radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that post‐harvest UV‐B treatments can improve, at least in selected genotypes, both the health‐promoting potential and the aesthetic properties of tomato and peach fruits by increasing anthocyanin contents . UV wavelengths may also affect other ripening‐related parameters, such as firmness, which, in strawberries, is affected by changes in the UV wavelengths transmitted by polythene films in protected cultivation . Similarly, tomato firmness was influenced by post‐harvest UV‐B treatments, either in a positive or in a negative way .…”
Section: Introductionmentioning
confidence: 99%
“…15 Fruit colour is also reported to be affected by the mean temperature in the growing season. 16 Light intensity has a large influence on metabolism of secondary metabolites, 17,18 firmness 19 and flavour of the fruit. 20 Also, phenological and biological properties such as floral initiation and number and length of nodes depend on solar radiation.…”
Section: Introductionmentioning
confidence: 99%